Complementary and alternative therapies in the palliative setting. Issue 10 (20th October 2022) - Martin, Jennifer H.; Patel, Joanne
Abstract: Complementary and alternative medicine (CAM) encompasses a wide range of medication, herbal, dietary and physical therapies that are not usually considered within the realm of conventional therapeutics. Approximately two thirds of the Australian population use CAMs and only around half of this number will discuss their use of these products with their doctor. Clinical use is commonly seen in patients with life‐limiting illness, often because they experience a high burden of symptoms. However, it is also the case that many of these therapies do not have demonstrated efficacy, particularly for the often broad list of conditions and symptoms for which they are chosen to be used. Further, depending on whether they are sold as medications, sold as food supplements or imported illegally and distributed via nonstandard therapeutic channels, several products have had reports of toxicity, severe adverse effects, batch irregularities and drug interactions with other therapies. This awareness, together with lack of standardisation of products and lack of interchangeability between brands has made prescribers unwilling to put patients at risk of harm by supporting their use. In this article, we cover general pharmacological principles around use of a small selection of chemicals used in a medical setting to enable some guidance for use.